Strategy for Developing the Narmada Lombok Cultural Heritage Park as a Sustainable Heritage Tourism Attraction - Mahawira, N. M. Gita Kundalini; Suasapha, Anom Hery; Dianasari, Dewa Ayu Lily (PT FORMOSA CENDEKIA GLOBAL, 2024)
Narmada Park Lombok is the oldest cultural heritage in West Lombok. The purpose of this study is to analyze the internal and external conditions of the Narmada Park Cultural Heritage using SWOT analysis. The informant determination technique is purposive sampling. The identification results found that there were 7 Strengths, 8 Weaknesses, 5 Opportunities and 3 Threats. Matching all of these things resulted in 4 sets of strategies, namely 3 SO Strategies (Strength - Opportunities), 5 ST Strategies (Strength - Threats), 4 WO Strategies (Weaknesses - Opportunities) and 3 WT Strategies (Weaknesses - Threats). The results of this study are that there needs to be collaboration between Narmada Park stakeholders to realize sustainable heritage tourism attractions.